Outbreak of Sudden Cardiac Deaths in a Tire Manufacturing Facility: Can It Be Caused by Nanoparticles? - Eun-A. Kim; Jungsun Park; Kun-Hyung Kim; Naroo Lee; Dae-Seong Kim; Seong-Kyu Kang (Elsevier, 2012)
Objectives: The purpose of this study was to review clinical characteristics and working environments of sudden cardiac death (SCD) cases associated with a tire manufacturer in Korea, and review possible occupational risk factors for cardiovascular disease including nanoparticles (ultrafine particles, UFPs). Methods: We reviewed (i) the clinical course of SCD cases and (ii) occupational and non-occupational risk factors including chemicals, the physical work environment, and job characteristics. Results: Possible occupational factors were chemicals, UFPs of rubber fume, a hot environment, shift work, overworking, and noise exposure. The mean diameter of rubber fume (63-73 nm) was (larger than diesel exhaust [12 nm] and outdoor dust [50 nm]). The concentration of carbon disulfide, carbon monoxide and styrene were lower than the limit of detection. Five SCD cases were exposed to shift work and overworking. Most of the cases had several non-occupational factors such as hypertension, overweight and smoking. Conclusion: The diameter of rubber fume was larger than outdoor and the diesel exhaust, the most well known particulate having a causal relationship with cardiovascular disease. The possibility of a causal relation between UFPs of rubber fume and SCD was not supported in this study. However, it is necessary to continue studying the relationship between large sized UFPs and SCD.